Bridge over troubled waters: Meeting the mental health needs of black students. (December 2014) - Cokley, Kevin; Cody, Brettjet; Smith, Leann; Beasley, Samuel; Miller, I.S. Keino; Hurst, Ashley; Awosogba, Olufunke; Stone, Steven; Jackson, Stacey
Meeting the mental health needs of black children will take more than just increasing access to mental health services and early identification. It also will require a critical evaluation of the practices and models being used to diagnose and treat mental health concerns. Frameworks have been established that use a positive, strengths-based, culturally appropriate approach in working with black children and adolescents. These models recognize that while black youth go through the same developmental processes as nonblack youth (e.g., puberty, identity, and maturation), culture and context play a unique role in their lives. School-based mental health clinics, wellness centers, and using peers as first responders are all proven solutions to help improve the mental health of not only black students but all students.